Correction: A revised mechanistic model for sodium insertion in hard carbons. Issue 5 (19th April 2021) - Au, Heather; Alptekin, Hande; Jensen, Anders C. S.; Olsson, Emilia; O'Keefe, Christopher A.; Smith, Thomas; Crespo-Ribadeneyra, Maria; Headen, Thomas F.; Grey, Clare P.; Cai, Qiong; Drew, Alan J.; Titirici, Maria-Magdalena
Abstract : Correction for 'A revised mechanistic model for sodium insertion in hard carbons' by Heather Au et al., Energy Environ. Sci., 2020, 13, 3469–3479, DOI: ; 10.1039/D0EE01363C .